2007
DOI: 10.1002/chin.200712277
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 as a Target for Drug Development

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Among Hsp90’s are key anti-apoptotic proteins, including Akt, Cdk4, Raf1 and Her2 71, 72. Inhibiting the binding of Hsp90 to ATP leads to proteasomal degradation of these substrates and corresponding anti-proliferative activity 50, 73, 74. In the context of our discussion, treatment with Hsp90 inhibitors has also been found to induce expression of Hsp70, likely through activation of HSF1 70.…”
Section: Roles Of Hsp70 In Diseasementioning
confidence: 69%
“…Among Hsp90’s are key anti-apoptotic proteins, including Akt, Cdk4, Raf1 and Her2 71, 72. Inhibiting the binding of Hsp90 to ATP leads to proteasomal degradation of these substrates and corresponding anti-proliferative activity 50, 73, 74. In the context of our discussion, treatment with Hsp90 inhibitors has also been found to induce expression of Hsp70, likely through activation of HSF1 70.…”
Section: Roles Of Hsp70 In Diseasementioning
confidence: 69%
“…HSP90 is reported to be a chemotherapeutic target molecule for many cancers, including CML 35,36,48,52. Some of the critical signaling molecules in Bcr-Abl+ cells are client proteins of HSP90 14,47,3.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that Hsp90 inhibitors accumulate in tumor cells more efficiently than in normal tissue leading to high differential selectivities 18,19. Currently, there are 26 Hsp90-targeted clinical trials in progress and these studies have demonstrated that Hsp90 can be inhibited at doses that are well tolerated by patients 20-23. Consequently, Hsp90 has emerged as a promising therapeutic target for the treatment of cancer because inhibition of Hsp90 results in the simultaneous degradation of multiple anti-cancer targets 11-14,23-24…”
Section: Discussionmentioning
confidence: 99%